2021
DOI: 10.1038/s41598-021-85396-y
|View full text |Cite
|
Sign up to set email alerts
|

Fish associations with shallow water subsea pipelines compared to surrounding reef and soft sediment habitats

Abstract: Offshore decommissioning activities are expected to increase as oil and gas subsea infrastructure becomes obsolete. Decisions on decommissioning alternatives will benefit from quantifying and understanding the marine communities associated with these structures. As a case study, fish assemblages associated with an inshore network of subsea pipelines located on the North West shelf of Western Australia were compared to those in surrounding natural reef and soft sediment habitats using remotely operated vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
3
9
1
Order By: Relevance
“…pipeline spans have been reported previously in the NW (McLean et al, 2017;Bond et al, 2018a;Schramm et al, 2021) and the North Sea (Redford et al, 2021). This pattern may also reflect known associations of this species with rocky habitat during the adult phase and soft habitat in the juvenile phase (Seiler et al, 2012).…”
Section: Fishery Target Species On Subsea Pipelines In Australiasupporting
confidence: 80%
“…pipeline spans have been reported previously in the NW (McLean et al, 2017;Bond et al, 2018a;Schramm et al, 2021) and the North Sea (Redford et al, 2021). This pattern may also reflect known associations of this species with rocky habitat during the adult phase and soft habitat in the juvenile phase (Seiler et al, 2012).…”
Section: Fishery Target Species On Subsea Pipelines In Australiasupporting
confidence: 80%
“…Across a tropical coastal seascape comprising coral reefs, mangroves, seagrass and sand, we found that sand habitats contributed more unique species to the total fish diversity across the seascape than would be expected based on their relatively lower species richness. While many studies have demonstrated that shallow (2–10 m depth) sand flats generally harbour fewer fish species than surrounding habitats (Gratwicke & Speight, 2005; Heck et al, 1989; Pittman et al, 2007; Schramm et al, 2021), especially of juveniles (Lefcheck et al, 2019), ours contributes to the growing literature demonstrating fundamental differences in community composition in unstructured/unvegetated habitats across both temperate (Henseler et al, 2019; Lingo & Szedlmayer, 2006; Staveley et al, 2017; Travers & Potter, 2002) and, to a lesser degree, tropical seascapes (Grimmel et al, 2020; Gullström et al, 2008; Hall & Kingsford, 2021). Further, when considered in the hierarchical context of local and regional diversity scales (Whittaker, 1960), sand flats had higher‐than‐expected contributions to between‐habitat β‐diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Slope values and sh feeding guilds were derived from the FishBase website (https://www. shbase.se/search.php) and relevant published literature (Schramm et al 2021). DOV's were not carried out across Fly reef due to limited days in the eld, but as there is no signi cant variation in habitat types between Eva and Fly reef (Dee et al 2020), and similar abundances have been witnessed at Fly reef previously (Pers.…”
Section: Fish and Urchin Abundancementioning
confidence: 99%